Neonatal Neuroprotection: Bringing Best Practice to the Bedside in the NICU. Issue 2 (March 2018) - Lockridge, Terrie
Abstract : Abstract: Preterm birth interrupts the precise process of fetal maturation, forcing critical neurologic growth to continue within the Neonatal Intensive Care Unit (NICU). Concern for the impact of the NICU experience on the developing brain led to a unit-based Quality Improvement (QI) project to promote best outcomes for our graduates. The objective was to implement a standard of care for neonatal neuroprotection in a large urban tertiary center. A multidisciplinary committee researched and developed the Neonatal Neuroprotective Best Practice Guidelines to identify optimal interventions, as well as provide physiologic rationales to reinforce importance of these practices. An educational initiative accompanied release of this document to support consistency in clinical practice and to stress the critical role that every caregiver played in a child's outcome. As the Best Practice Guidelines encompassed virtually all aspects of caregiving in the NICU, it was impractical to measure the impact of such a broad range of interventions in a methodical manner. The full effect of these interventions will not likely be evident until NICU graduates have grown into childhood and adolescence. These constraints limited the scope of this QI project to the practicalities of identifying neuroprotective best practice and bringing it to the bedside. When combined with evidence-based medical and nursing care, neuroprotective care represents the best means of facilitating normal development and minimizing disability for our NICU graduates. Abstract : Concern for the impact of the NICU experience on the developing infant brain led to a unit-based quality improvement project to promote best neonatal outcomes. A multidisciplinary committee evaluated current evidence and developed the Neonatal Neuroprotective Best Practice Guidelines to identify optimal interventions, as well as provide physiologic rationales to reinforce importance of the practices for the clinical team. The process of developing and implementing the guidelines are presented.